Philosophy, Rhetoric, and Sophistry in the High Roman Empire : Maximus of Tyre and Twelve Other Intellectuals - Lauwers, Jeroen (Mnemosyne, Supplements Ser, 2015)
Contents -- Acknowledgements -- Introduction -- Scholarly Reception -- From the Collective to the Individual -- From Macrolevel to Microlevel -- Why Maximus? -- Chapter 1. Philosophy, Rhetoric, and Sophistry in the Roman Empire -- 1. The Traditional Conflict: A Short Overview -- 2. Greco-Roman Imperial Culture -- 3. A Functionalist Approach -- 4. Individual Authors -- Chapter 2. The dialexeis of Maximus of Tyre -- 1. Reading Maximus' dialexeis -- 2. Communication and Pedagogy -- 3. Sophistry -- 4. Rhetoric -- 5. Philosophy -- 6. Purpose and Meaning -- 7. Analysis of Individual dialexeis -- Conclusion -- Bibliography -- 1. Text Editions of Primary Sources: Maximus of Tyre -- 2. Text Editions of Primary Sources: Others -- 3. Translations, Commentaries, Studies -- Index Locorum -- Index of Persons and Concepts.